1997
DOI: 10.1177/082957359701200212
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary School Teams: A Five-Year Follow-up Study

Abstract: Toronto Board of EducationA total of 341 multidisciplinary staff members in 55 elenwntary and secondary schools participated in a 1995 study that identified the characteristics of students referred to school teams. The study was in part a replication of one done in 1990, with additional focus on team recommendations formulated during consultation. Many of the findings indicate that over the past five years, teams continued to focus on the same needs and the same model of service. The number of individual stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Expanded team mandates can include consultative services to staff, parents and community agencies. In their five-year follow up study on school teams, Cole and Brown (1996) found that teams continue to be utilised for consultation about immigrant and refugee students, particularly around the common difficulties in coping with adjustment to a new language and culture. About a quarter of those surveyed saw refugee needs as an attribute that was most often related to student referral for team consultation.…”
Section: Resultsmentioning
confidence: 99%
“…Expanded team mandates can include consultative services to staff, parents and community agencies. In their five-year follow up study on school teams, Cole and Brown (1996) found that teams continue to be utilised for consultation about immigrant and refugee students, particularly around the common difficulties in coping with adjustment to a new language and culture. About a quarter of those surveyed saw refugee needs as an attribute that was most often related to student referral for team consultation.…”
Section: Resultsmentioning
confidence: 99%